1997
DOI: 10.1021/ef960113x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon on Air Entrainment in Fly Ash Concrete:  The Role of Soot and Carbon Black

Abstract: The most important commercial outlet for coal ash is in the concrete industry as a partial replacement for Portland cement. In many concrete mixtures careful control of air entrainment is required, but the presence of solid carbon disrupts the air entrainment process. An earlier study focused on the fundamental role of carbons, which were found to adsorb air-entraining admixtures, the specialty surfactants used in concrete mixtures, rendering them less active for their primary function as stabilizing agents fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 3 publications
4
58
0
1
Order By: Relevance
“…The surfactant adsorption capacity of the treated and untreated carbon black samples was determined by titration procedure referred to as the foam index test [18,21]. Foam index measurements involved placing the test carbon sample [usually about 90 mg] together with 8 grams of Portland cement and 25 ml of de-ionized water into a 70 ml cylindrical jar with a 40 mm I.D., 80 mm length.…”
Section: Methodsmentioning
confidence: 99%
“…The surfactant adsorption capacity of the treated and untreated carbon black samples was determined by titration procedure referred to as the foam index test [18,21]. Foam index measurements involved placing the test carbon sample [usually about 90 mg] together with 8 grams of Portland cement and 25 ml of de-ionized water into a 70 ml cylindrical jar with a 40 mm I.D., 80 mm length.…”
Section: Methodsmentioning
confidence: 99%
“…"Ash #1": A commercial carbon-containing fly ash from bituminous coal combustion at the full scale. The fly ash is sample FA21 in the Brown University sample bank with 6.3% loss on ignition (approximately 6.3% elemental carbon), which has been used in previous studies [5,6]. 5.…”
Section: Methodsmentioning
confidence: 99%
“…In recent studies, surfactant adsorption on carbon has been identified as a key phenomenon determining the suitability of coal combustion fly ash as a concrete additive [5][6][7][8][9]. Here the carbon is a contaminant and its undesirable adsorption of surfactant from the aqueous concrete paste reduces the surfactant's ability to stabilize sub-millimeter air bubbles that help improve freeze-thaw resistance in set concrete [10].…”
Section: Introductionmentioning
confidence: 99%
“…Controlled ozone concentrations from 500 ppm -2 vol-% were generated in air and passed upward through fixed beds of ash (50 -200 gms), for fixed contact times (1 minute -20 hrs), while outlet ozone concentration was monitored in real time. The ozonated ash samples were removed and a standard surfactant adsorptivity determined by a simple titration procedure used previously [3]. Additional experiments were carried out on carbon black under the same ozonation conditions as an inorganic free model carbon for suitable for more detailed surface characterization.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of interaction between an AEA and a specific fly ash or carbon solid sample can be estimated using the foam index test [3], a simple laboratory titration procedure. This procedure was used in this study to investigate the interactions between a commercial AEA (Darex II, trademark of W.R. Grace & Co., Cambridge, MA) and a variety of model carbonaceous materials and carboncontaining fly ash samples.…”
Section: Surfactant Titrationmentioning
confidence: 99%